Uzbekistan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in the Republic of Uzbekistan during 1992-97. It compares growth in Uzbekistan with that of other transition economies and seeks to shed light on why Uzbekistan has suffered a smaller transformational recession than other transition economies. The paper covers the existing arrangements for production and trade in agriculture, and estimates the costs for agriculture arising from state procurement and the multiple exchange rate system. The paper also traces the effects of multiple exchange rates and other quasi-fiscal operations on the economy as a whole.